An Energy Harvester for Low‐Frequency Electrical Signals. Issue 6 (26th April 2020) - Wang, Xin; Wilson, Peter R.; Leite, Ricardo B.; Chen, Guiyou; Freitas, Helena; Asadi, Kamal; Smits, Edsger C. P.; Katsouras, Ilias; Rocha, Paulo R. F.
Abstract : Generating electricity from low‐frequency mechanical agitations produced by ocean waves, plants, or human motion is emerging as a key, environmentally friendly technology in combating harmful emissions caused by burning fossil fuels. The electric pulses generated by the appropriate transducers, such as triboelectric or piezoelectric generators, have to be rectified and stored in a sustainable external circuit. The bottleneck, however, is the harvesting circuitry, which relies on rather expensive up‐conversion oscillation technologies. Such circuits are primarily designed and optimized for frequencies well above the kHz range, much higher than the aforementioned mechanical stimuli, and are therefore energy demanding. Herein, a sustainable energy harvester is developed that alleviates the need for using up‐conversion and allows efficient harvesting of energy from low‐frequency voltage pulses, such as the ones typically generated by triboelectric or piezoelectric generators. The resonant circuit is designed to match overall response originating from such low‐frequency oscillating energy sources. The design enables the harvester to be operable at frequencies as low as 1 Hz. Computer aided design simulations are demonstrated, which are miniaturized harvesters on a printed‐circuit board using low‐cost components, and scalability of the proposed design is discussed, which paves the way to affordable, efficient, and sustainable low‐cost energy solutions. Abstract : A technology to harvest energy from low‐frequency sources is devised, eliminating the need for up‐conversion techniques. This is accomplished by modeling and tuning the resonant frequency of an energy‐harvesting system, which comprises a step‐up transformer and a boost converter on a miniaturized printed circuit board prototype.